1991
DOI: 10.2116/analsci.7.229
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection-Spectrophotometric Determination of Trace Amounts of Iodide by Its Catalytic Effect on the 4,4-Bis(dimethylamino)-diphenylmethane-Chloramine T Reaction

Abstract: A flow injection analysis method is proposed for the spectrophotometric determination of trace amounts of iodide based on its catalytic effect on the oxidation of 4,4'-bis(dimethylamino)diphenylmethane (tetrabase) by Chloramine T in a weakly acidic solution. Iodide in water samples can be determined at a sampling rate of 85 h-1 with 300 µl sample injections. The detection limit is 0.1 µg 1-1 and the calibration graph for iodide is linear up to 2.tg 1-1, showing a slightly negative deviation in the higher conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Iodate reduction activity was evaluated by the amount of I − reduced from IO − 3 by 1 g (FW) of excised roots per hour. I − concentration in the buffer was determined by 4,4′-methylenebis( N,N -dimethylaniline)-chloramine T reaction (Yonehara et al, 1991). To evaluate the net I − concentration reduced from IO − 3 by excised roots, the concentration of I − in the IO − 3 -free buffer incubated with excised roots was also determined as I − derived from excised roots during incubation, and subtracted from I − concentration in the IO − 3 buffer incubated with excised roots.…”
Section: Methodsmentioning
confidence: 99%
“…Iodate reduction activity was evaluated by the amount of I − reduced from IO − 3 by 1 g (FW) of excised roots per hour. I − concentration in the buffer was determined by 4,4′-methylenebis( N,N -dimethylaniline)-chloramine T reaction (Yonehara et al, 1991). To evaluate the net I − concentration reduced from IO − 3 by excised roots, the concentration of I − in the IO − 3 -free buffer incubated with excised roots was also determined as I − derived from excised roots during incubation, and subtracted from I − concentration in the IO − 3 buffer incubated with excised roots.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity is not as good as other flow injection methods, e.g., a catalytic spectrophotometric flow injection method has a reported detection limit of 0.1 mg l 21 iodide. 11 The method described here is, however, highly selective to iodide, as no matrix effects or interferences other than sulfide were found. The flow injection method is simpler, easier to use and more rapid than the manual batch methods.…”
Section: Discussionmentioning
confidence: 83%
“…Manual methods for iodide determination are usually tedious; however, flow injection analysis represents an interesting method for automation. 5 Several flow injection methods for determination of iodide based on spectrophotometric, [6][7][8] potentiometric 9,10 and catalytic spectrophotometric detection 11,12 have been reported. Motomizu and Yoden 13 reported a tubular microporous PTFE membrane that was applied to the permeation of chlorine, bromine and iodine.…”
mentioning
confidence: 99%
“…Yonehara et al investigated the contamination of iodine from ambient air in the laboratory. 8 They reported that 50 cm 3 of pure water in a beaker caused iodine concentration, even after several minutes of standing time, and that the concentration became progressively higher with prolonged standing.…”
Section: Procedures For Acid Digestionmentioning
confidence: 99%